Allergen quantitative risk assessment within food operations: Concepts towards development of practical guidance based on an ILSI Europe workshop. (August 2022) - Remington, Benjamin C.; Baumert, Joseph; Blom, W. Marty; Bucchini, Luca; Buck, Neil; Crevel, René; De Mooij, Fleur; Flanagan, Simon; Hindley, James; Javed, Bushra; Stavropoulou, Despoina Angeliki; van den Dungen, Myrthe W.; et al.
Abstract: Quantitative risk assessment (QRA) for allergens exists in many different forms with different requirements placed on the risk assessor depending on the question that needs to be answered. An electronic workshop held in October 2020 and comprising representatives from a wide range of food allergy and allergen stakeholder groups identified that a summary of current best in class guidance, identified gaps, potential improvements & harmonization of allergen QRA arising largely from cross contact would be very beneficial. The current manuscript provides an introduction to allergen QRA and an overview of inputs potentially needed for different QRA methods, when deemed feasible and necessary. It also introduces the European branch of the International Life Sciences Institute (ILSI Europe) Expert Group (EG), created to attempt to achieve consensus on the methodologies needed for allergen QRAs by food business operators, and their implementation. Areas of focus include proactive assessments for food production under normal conditions, both in the upstream supply chain and in food production facilities, and reactive assessments as part of an allergen incident response. As a follow-up report to the October 2020 electronic workshop, the current manuscript provides an overview of allergen QRA and insights into the guidance being developed. This manuscript will itself be followed by more detailed guidance for allergen QRA published open access as an ILSI Europe report. Highlights: Quantitative risk assessment (QRA) for allergens exists in many different forms. Where QRA is feasible and useful, availability of required inputs & data is favored. Work Group 1: best ways to obtain & convey reliable information across supply chain. Work Group 2: assess allergen cross-contact in food production in normal conditions. - Work Group 3: systematic and harmonized approach for applying QRA in 'incidents'.